INTERPERSONAL COMMUNICATION AS A DETERMINANT OF AUDIT FINDINGS AND AUDIT JUDGMENT: A CONCEPTUAL MODEL FOR NATURAL RESOURCE AUDITS IN INDONESIA'S FRONTIER REGIONS - Sally Paulina Sandanafu (CV KULTURA DIGITAL MEDIA, 2026)
Natural resource audits conducted by Supreme Audit Institutions in resource-rich, geographically remote subnational regions present distinctive interpersonal demands that remain undertheorized in the auditing literature. Drawing on the professional skepticism literature, communication theory, and public-sector audit quality research, this paper develops a conceptual model linking auditor interpersonal communication competence to audit evidence quality, audit findings, and audit judgment, moderated by contextual factors specific to frontier (3T) regions, geographic isolation, resource dependency, and local institutional culture. Using Indonesia's Audit Board (Badan Pemeriksa Keuangan/BPK) and the emerging natural-resource audit context of Kepulauan Tanimbar Regency, Maluku Province site of the Masela Block LNG development as an illustrative empirical setting, the paper synthesizes existing theory into an integrated model and derives testable propositions to guide future empirical research. The paper contributes a theory-building foundation for an underexamined intersection of interpersonal communication and public-sector audit judgment, and offers a practical agenda for auditor capacity development in extractive-resource, frontier-region audit contexts.